Subnational Public Expenditure and Financial Accountability Assessment, 2019 : Ukraine, Iziaslavskyi Rayon - World Bank (World Bank, Washington, DC, 2021)
This Public Expenditure and Financial Accountability (PEFA) 2019 report is an assessment of the quality of the Ukrainian PFM system at the subnational level. More specifically, the PEFA assessment measures which processes and institutions contribute to the achievement of desirable budget outcomes, aggregate fiscal discipline, strategic allocation of resources, and efficient service delivery. A central government PEFA assessment and a subnational assessment at the oblast level were conducted in 2019. The main purpose of the 2019 PEFA assessment is to provide the government of Ukraine with an objective, up-to-date diagnostic of public financial management performance at the rayon level of subnational government based on the latest internationally recognized PEFA methodology. This assessment covers the Iziaslavskyi rayon administration which is composed of sixteen budgetary institutions.